A cross-cultural investigation of the functional theory of human values : examining its structure and prediction of external outcomes : a thesis submitted to Massey University in fulfilment of the requirements for the degree of Doctor of Philosophy in Psychology - Vilar Lobo de Souza, Roosevelt (Massey University, 2020)
The present thesis examines the Functional Theory of Human Values in a multi-nation approach. This theory has a claim of parsimony and attempts to explain data from more complex models reported in the literature (Gouveia, Milfont, & Guerra, 2014). However, most of the research using this theory is limited to the Brazilian context. Through four systematic cross-sectional investigations and using the Functional Theory, the present thesis shows (1) an examination of the structure of values, (2) age, and gender differences in values priorities, and (3) values prediction of external outcomes in a multi-nation approach. Study 1 demonstrated that the dimensionality of values is identified using confirmatory multidimensional scaling, and promising results are reported using confirmatory factor analysis with a Bayesian estimation. This study also provides evidence of cross-cultural equivalence using the approximate Bayesian invariance approach and the alignment method. Study 2 demonstrated that patterns of values change over the life span vary in a linear way for almost all the six factors that give structure to the Functional Theory. This study showed that the variation in value importance varies in a harmonic way, mirroring the hypothesis of congruence proposed by Gouveia: that values with similar goals vary in the same direction. This study also showed that values with an interpersonal focus are given more importance from older people and women, and that values with an egocentric focus are given less importance the older the participants get. Men score higher than women in almost all life stages for values with egocentric focus. Study 3 focused on the prediction of values. This study demonstrated a plausible process in which values operate via social capital in influencing people to be more politically active. Study 4 was also focused on the prediction of values, and it showed fresh evidence for the role of values to predict carbon emission concerns. Using multi-level analysis, this shows that existence and suprapersonal values are the main predictors of carbon emission concerns, and that meaningful cross-level interactions are identified. Overall, this thesis contributes with the field of values by presenting cross-cultural evidence of structure and prediction of a parsimonious model of values.
Keywords: Values; Cross-cultural studies; 520599 Social and personality psychology not elsewhere classified